Implementation of Double Track System in Conviction Towards Special Expertise Crime - Ahmad Aditya Putra Utama; Heru Suyanto (Ius Poenale, 2021)
Sentencing must be guided by the principle of quae sunt minoris culpae sunt majoris infamiae (cruel crimes will be punished with cruel punishment). However, there must be a limit to the punishment (poenae sunt restringenade). In its implementation, the imposition of crimes against convicted people often creates ongoing problems in people's lives. Instead of aiming to popularize the convicts, in fact the imposition of crimes often causes suffering to the perpetrator and even his family. This study aims to determine the basis for justifying the imposition of sanctions in the punishment of criminals with special skills and to formulate the ideal concept of punishment for convicts with special skills in the future. This research is a normative legal research; the data source in this study uses secondary data consisting of primary legal materials, secondary legal materials, and tertiary legal materials. The approach in this research uses a statutory approach, a comparative approach and a conceptual approach. Based on the results of the study, it shows that the basis for justifying the imposition of sanctions for criminal acts with special expertise is the Mark system of penalties. The use of the Double Track System in the punishment of convicts who have special expertise in the field of science so that it is in line with the criminal purpose of providing education, in addition to being convicted with the main crime, the convict is also subject to acts in the form of social work by teaching/transforming the knowledge/expertise possessed to people, many through certain educational/research institution/institutions online (on line).